Capitalizing on mobile technology to support healthy eating in ethnic minority college students. Issue 2 (17th February 2016) - Rodgers, Rachel F.; Pernal, Wendy; Matsumoto, Atsushi; Shiyko, Mariya; Intille, Stephen; Franko, Debra L.
ABSTRACT: Objective : To evaluate the capacity of a mobile technology–based intervention to support healthy eating among ethnic minority female students.Participants : Forty-three African American and Hispanic female students participated in a 3-week intervention between January and May 2013.Methods : Participants photographed their meals using their smart phone camera and received motivational text messages 3 times a day. At baseline, postintervention, and 10 weeks after the intervention, participants reported on fruit, vegetable, and sugar-sweetened beverage consumption. Participants were also weighed at baseline.Results : Among participants with body mass index (BMI) ≥25, fruit and vegetable consumption increased with time ( p < .01). Among participants with BMI <21, consumption of fruit decreased ( p < .05), whereas the consumption of vegetables remained stable. No effects were found for sugar-sweetened beverage consumption.Conclusion : Mobile technology–based interventions could facilitate healthy eating among female ethnic minority college students, particularly those with higher BMI.